Alterations in mitochondrial morphology of Schizosaccharomyces pombe induced by cell-death promoting agents - Pevala, V; Kolarov, J; Polcic, P (Folia microbiologica, 2007)
The effect of the yeast cell-death inducing agents, Bax and acetic acid, on mitochondrial structure of Schizosaccharomyces pombe was studied. Comparison of mitochondrial structures in cells grown on different substrates and visualized with different probes revealed variations in their morphology. Cells grown on respiratory C sources as well as in the presence of antimycin A exhibited punctuated mitochondria when visualized with mitochondrially targeted green fluorescent protein, while they still appeared as tubular structures when stained with DiOC6(3). Both expression of Bax and acetic acid treatment induced fragmentation and aggregation of mitochondrial network, which could be prevented by coexpression of Bcl-XL. Aberrant mitochondrial morphology generated by either Bax or acetic acid was not accompanied with the loss of mitochondrial genome (mtDNA), indicating that alterations of mitochondrial morphology following death stimuli follow different mechanisms than those involved in mitochondrial inheritance mutants.
Keywords: DNA fungální; Mitochondria; Blotting, Southern; DNA, Fungal; Microscopy, Fluorescence; Transformation, Genetic; transformace genetická; zelené fluorescenční proteiny; mitochondriální DNA; DNA, Mitochondrial; fluorescenční mikroskopie; Green Fluorescent Proteins; buněčná smrt; Schizosaccharomyces; Carbocyanines; mitochondrie; plazmidy; kyselina octová; Acetic Acid; Southernův blotting; bcl-2-Associated X Protein; protein X asociovaný s bcl-2; Plasmids; Cell Death; karbocyaniny